The Night Wolves : Klub Motor Patriotis Milik Rusia - Muhammad Fahmi Hawari Nasution (Jurnal Sentris, 2019)
In February 2014, The Night Wolves Motorcycle Club, Rusia’s first and largest Motorcycle Club, became one of the Non-state Actors who played a role in Rusia’s military operation to annex Crimea although in 1989 they protested against the Soviet Union governance and called for freedom of the people. This paper aimed to explore the evolution of the Night Wolves Motorcycle Club from the protester of Russia’s government to a patriotic organization who support the government, describe the ideology of the Night Wolves motorcycle club, and analyzes the role of the Night Wolves motorcycle club in Ukraine. In addition, this article will explore the Rusian’s “Putin’s Sistema” as a way to outsource the non-state actors to help Rusia in any of its policy which talks about the reason why an actor in international scope is doing something based on its ideology and norm. This paper will use social movement as its theory.